Fundamentals of Entrepreneurship (ENT300) : Business plan report cheezychicks food & stall / Ezmith Ujang Syah Khairulhizam … [et al.]. - Khairulhizam, Ezmith Ujang Syah; Ahmad, Mohd Ridwan; Saimon, Nur Shafina; Mohammad Suhaili, Nur Suhadda; Abdul Hamid, Siti Nurhamizah (2019)
CheezyChicks is established as a partnership business which is among five person. The organization of CheezyChicks consists of General Manager which is Nur Shafina Binti Saimon, Administrative Manager which is Nur Suhadda Binti Mohammad Suhaili, Operational Manager which is Ezmith Ujang Syah Bin Khairulhizam, Marketing Manager which is Mohd Ridwan Bin Ahmad, and Financial Manager which is Siti Nurhamizah Binti Abdul Hamid. CheezyChicks have been choose because we have been inspired by the entrepreneur that we have been interviewed for our case study assignment. His business is gaining popularity among young people and that is one of the reason why we established this business.